2020 7th International Conference on Control, Decision and Information Technologies (CoDIT) 2020
DOI: 10.1109/codit49905.2020.9263959
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical model of information signals formation at the physical layer in FANET

Abstract: Creation of reliable and efficient flying ad-hoc networks (FANET) requires detailed development of the model of the physical layer of data transmission, determined by the conditions of operation of the networks. The problems of well-known software simulators of communication networks are the simplified nature of the physical layer, as well as the inability to obtain specific analytical solutions in the process of simulation. The hierarchical model of formation of information signals which allows to represent v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This is one of the most distinguishing characteristics of FANET enabling it to be suitable for trajectory control and optimization. Besides, power consumption [31], [32], localization [33], [34] and radio propagation models [35], [36] have been found as other critical factors with a huge impact on the performance of FANETs.…”
Section: Background Of Fanetmentioning
confidence: 99%
See 1 more Smart Citation
“…This is one of the most distinguishing characteristics of FANET enabling it to be suitable for trajectory control and optimization. Besides, power consumption [31], [32], localization [33], [34] and radio propagation models [35], [36] have been found as other critical factors with a huge impact on the performance of FANETs.…”
Section: Background Of Fanetmentioning
confidence: 99%
“…Herein, a hierarchical model in [36] showed that the physical layer has a significant impact on the efficiency of FANET networks. It detailed signal propagation of different bands, including sub-6GHz and mmWave bands in different levels of the atmosphere; signal creation and conversion in FANET transceivers; and signal conversion in antennas.…”
Section: B Physical Layer Advancements In Fanetsmentioning
confidence: 99%